2015
DOI: 10.1105/tpc.15.00489
|View full text |Cite
|
Sign up to set email alerts
|

Functional Conservation in the SIAMESE-RELATED Family of Cyclin-Dependent Kinase Inhibitors in Land Plants

Abstract: The best-characterized members of the plant-specific SIAMESE-RELATED (SMR) family of cyclin-dependent kinase inhibitors regulate the transition from the mitotic cell cycle to endoreplication, also known as endoreduplication, an altered version of the cell cycle in which DNA is replicated without cell division. Some other family members are implicated in cell cycle responses to biotic and abiotic stresses. However, the functions of most SMRs remain unknown, and the specific cyclindependent kinase complexes inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
128
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(137 citation statements)
references
References 59 publications
7
128
2
Order By: Relevance
“…18,20,21 Of particular note, Kumar and coworkers found that 10 different SMRs, including an SMR from the bryophyte Physcomitrella patens, can complement the trichome cell division phenotype of Arabidopsis sim mutants. 13 Additionally, individual KRP and the SMR genes show distinct patterns of tissue-specific and stress-regulated expression, consistent with the individual genes playing roles in integrating the cell cycle with a wide variety of signals. 12,22,23 This level of transcriptional control is presumably secondary to the post-transcriptional control of CKI protein levels acting within the cell cycle itself that was described in the previous section.…”
Section: Krps and Smrs Play Diverse Roles In Plant Growth And Developmentioning
confidence: 59%
See 4 more Smart Citations
“…18,20,21 Of particular note, Kumar and coworkers found that 10 different SMRs, including an SMR from the bryophyte Physcomitrella patens, can complement the trichome cell division phenotype of Arabidopsis sim mutants. 13 Additionally, individual KRP and the SMR genes show distinct patterns of tissue-specific and stress-regulated expression, consistent with the individual genes playing roles in integrating the cell cycle with a wide variety of signals. 12,22,23 This level of transcriptional control is presumably secondary to the post-transcriptional control of CKI protein levels acting within the cell cycle itself that was described in the previous section.…”
Section: Krps and Smrs Play Diverse Roles In Plant Growth And Developmentioning
confidence: 59%
“…[15][16][17] In contrast, while SIM overexpression can induce endoreplication, resulting in DNA contents as high as 128C, overexpression of SIM or other SMRs has never been observed to inhibit DNA replication or cause cell death. 8,13 Thus, available evidence indicates that SMRs only inhibits M-phase, while KRPs can block entry into both M-and S-phases.…”
Section: Smrs and Krps Play Overlapping But Distinct Roles In The Celmentioning
confidence: 99%
See 3 more Smart Citations